2019
DOI: 10.1103/physrevlett.123.194501
|View full text |Cite
|
Sign up to set email alerts
|

Flow Resistance and Structures in Viscoelastic Channel Flows at Low Re

Abstract: The flow of viscoelastic fluids in channels and pipes remain poorly understood, particularly at low Reynolds numbers. Here, we investigate the flow of polymeric solutions in straight channels using pressure measurements and particle tracking. The law of flow resistance is established by measuring the flow friction factor fη versus flow rate. Two regimes are found: a transitional regime marked by rapid increase in drag, and a turbulent-like regime characterized by a sudden decrease in drag and a weak dependence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(92 citation statements)
references
References 41 publications
8
82
2
Order By: Relevance
“…With the increase of flowrate and polymer concentration, flow instability transits from weak bifurcation instabilities to dramatically chaotic turbulence. Our results show strong evidence for the "instability upon an instability" mechanism mentioned by Qin et al [40] and provide a new method and device for the simplest mixing enhancement in micro channels without plenty of additions. We prove experimentally that the orthogonal injection is beneficial to achieve efficient mixing within a shorted mixing path.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…With the increase of flowrate and polymer concentration, flow instability transits from weak bifurcation instabilities to dramatically chaotic turbulence. Our results show strong evidence for the "instability upon an instability" mechanism mentioned by Qin et al [40] and provide a new method and device for the simplest mixing enhancement in micro channels without plenty of additions. We prove experimentally that the orthogonal injection is beneficial to achieve efficient mixing within a shorted mixing path.…”
Section: Discussionsupporting
confidence: 75%
“…Addressing such limitations, we propose a new approach of enhancing mixing by combining the advantages of serpentine channel and abrupt contraction micro channel, i.e., a simple orthogonal injection into a micro serpentine channel, that results in a very short mixing length. Such an approach is similar to the work of Qin et al [40] in the straight channel with a set of small cylinders at the entrance section. In this work, we prove experimentally that the orthogonal injection is a good bridge to connect the homogeneity on mixing wanted by the smallest scale fluctuation and the elastic instabilities, which is dominated by the large-scale fluctuations.…”
Section: / 26mentioning
confidence: 87%
“…Although it is well documented (3,(6)(7)(8)(9)(10), the anomalous flow resistance exhibited by polymer solutions in porous media has evaded explanation for over half a century. Many have speculated that this phenomenon is due to the onset of elastic turbulence, given that elastic instabilities have been reported to generate increased flow resistance in a range of simplified geometries (7,(17)(18)(19)(20)(21)33). However, a quantitative link between the associated flow fluctuations in a porous medium-if they exist-and the macroscopic flow resistance has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…This anomalous increase in flow resistance is often thought to reflect the accumulated extension of individual polymer molecules as they are transported through constrictions of the pore space (11)(12)(13)(14)(15), although direct validation of this idea remains lacking. Some recent simulations (16) and experiments in ordered 2D geometries (7,(17)(18)(19)(20) have instead suggested that this anomalous increase in flow resistance is linked to the onset of an elastic instability, arising from the buildup of polymer-induced elastic stresses during transport. These instabilities are well studied in a range of simplified geometries (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) and can generate chaotic flow fields reminiscent of those observed in inertial turbulence (20,28,33)-often termed "elastic turbulence."…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of this seminal effect at the beginning of the new millennium 1 , research is ongoing [10][11][12][13][14][15][16] . The transition to elastic turbulence is accompanied by an enhanced drag resistance in flowing polymer solutions 1,2,4,15 . In this work we report on the rich complex behaviour initiated in viscoelastic flows by applying an active open-loop control scheme in the form of a timemodulated shear rate.…”
mentioning
confidence: 99%